A study to assess the practice of incentive spirometer among postoperative patients at a tertiary level care hospital - Batra, Akashdeep; Kalyani, Vasantha (Indian Journal of Nursing Sciences, 2024)
Background: Incidence shows that 17% to 88% of people will have decreased lung volumes after surgery. This can be made less sever and less likely by use incentive spirometer. An incentive spirometer is routinely considered a part of the perioperative respiratory therapy strategies to prevent or treat complications and helps improve the functioning of lungs. Aims: The role of incentive spirometry is well established for preventing post-operative pulmonary complications but there is lack of evidence regarding its use and compliance in patients. The main aim of this study is to assess the practice of incentive spirometry amongst the post-operative patients. Methods and materials: It is a Case series type of descriptive observational study carried out on post-operative patients in a tertiary care hospital using a checklist for three consecutive post-operative days. Results: On day 1, only 8% of the patients performed adequately while 52% were moderately adequate and 40% were inadequate in performance. On day 2, 30% were adequate, 58% were moderately adequate while 12% had inadequate performance. On day 3, 64% of the patients performed adequately 32% were moderately adequate while 4% still had inadequate performance. Conclusion: It is concluded that practice and use of incentive spirometry improved in the period of three days. Patients were able to perform better and were more competent in the practice. The compliance improved on day third as compared to day one and patients were able to perform the steps adequately.